A Semi-synthetic Oligosaccharide Conjugate Vaccine Candidate Confers Protection against Streptococcus pneumoniae Serotype 3 Infection. Issue 11 (17th November 2016) - Parameswarappa, Sharavathi Guddehalli; Reppe, Katrin; Geissner, Andreas; Ménová, Petra; Govindan, Subramanian; Calow, Adam D.J.; Wahlbrink, Annette; Weishaupt, Markus W.; Monnanda, Bopanna Ponnappa; Bell, Roland Lawrence; Pirofski, Liise-Anne; Suttorp, Norbert; et al.
Summary: The identification of immunogenic glycotopes that render glycoconjugate vaccines protective is key to improving vaccine efficacy. Synthetic oligosaccharides are an attractive alternative to the heterogeneous preparations of purified polysaccharides that most marketed glycoconjugate vaccines are based on. To investigate the potency of semi-synthetic glycoconjugates, we chose the least-efficient serotype in the current pneumococcal conjugate vaccine Prevnar 13, Streptococcus pneumoniae serotype 3 (ST3). Glycan arrays containing synthetic ST3 repeating unit oligosaccharides were used to screen a human reference serum for antibodies and to define the recognition site of two ST3-specific protective monoclonal antibodies. The glycan array screens identified a tetrasaccharide that was selected for in-depth immunological evaluation. The tetrasaccharide-CRM197 carrier protein conjugate elicited protective immunity as evidenced by opsonophagocytosis assays and protection against pneumonia caused by ST3 in mice. Formulation of the defined protective lead candidate glycotope has to be further evaluated to elicit optimal long-term immunity. Graphical Abstract: Highlights: Glycan arrays reveal epitopes of two monoclonal antibodies to S. pneumoniae 3 CPS CRM197 conjugates of one identified tetrasaccharide antigen are immunogenic in mice Vaccination with the glycoconjugates protects mice from pneumococcal pneumonia Abstract : Parameswarappa et al. describe a synthetic immunogenic tetrasaccharide hapten of the capsular polysaccharide of Streptococcus pneumoniae serotype 3. Glycoconjugates of this antigen are able to protect mice from pneumococcal pneumonia in a lethal transnasal challenge model.